Ocorrência e flutuação populacional de afídeos (Homoptera: Aphididae), na cultura da alfafa (Medicago sativa L.) em Lavras, MG - Carvalho, Alessandra Ribeiro de (1995)
The objetive of this work was to do a survey in a alfalfa crop (Medicago sativa L.) crioula variety in Lavras, Minas Gerais state, to determine the occurrence of aphids species. The weather and plant cutting effects on these aphids populations were evaluated. The survey was carried out weekly from March, 1993 to February, 1994. It was observed the occurrence of Therioaphis trifolii form maculata, Acyrthosiphon kondoi, A. pisum and Aphis craccivora. The faunistic index (constancy) for each aphid species occurring during the survey period was analysed. Aphis craccivora was considered accidental being found in only two collections; the other species were constant. The weather effects on population fluctuaction through graphic analises showed a tendency to occurr high populations of 7. trifolii f. maculata on temperatures near to 25° C, and was observed a predominance of this specie over the other species in 75% of collections. The two Acyrthosiphon species, by contrast, increased in number when temperature decreased below 20° C, with a peak in August for both species. When the regression analisys was made, the weather effects were not significant for T. trifolii f. maculata population. For Acyrthosiphon species, only temperature showed significative effect, although the correlation was iower. It was observed a low occurrence of A. pisum during all year, but in some weeks of March, June, November and December the occurrence was nil. The three species of aphids of highets incidence in the alfalfa crop were separated in five groups, formed of nimphs and aduits with and without wings, and 76,04% of total aphids were in first and second stages. As to the ramaining insects, 21,65% were without wings and 2,31 % alate, indicanting a high mortality of young nymphs. The non-parametric statistics and Friedman's test at 5% used to determine significant diferences between species collected and between instars, led to the conclusion that populations of the three species were statisticaly different. The cutting of alfalfa to produce hay decreased the aphid populations, although the population increased quickly afterwards. The other effects, beside cutting and weather may influence the aphids population, such as natural enemies observed in the field.